The Role of CKPT in Bridging Perceived and Actual Cognitive Health in Aging Population - Shimura T; Okuyama E; Suzuki A; Ohsugi H (Contemporary Research and Perspectives in Biological Science Vol. 9, 2025)
Objective: CKPT (Color Kanji Pick-out Test) is the newly devised neuropsychological test which can be classified as a slight decline level in the stage of PCSD (Preclinical Stage of Dementia or MCI (Mild Cognitive Impairment). Such classification cannot be done by conventional neuropsychological tests such as MMSE (Mini-Mental State Examination) and CDR (Clinical Dementia Rating). As the evidences and the diagnosis criteria of CKPT was already established, the purpose is this research is to apply it to self-proclaimed people with healthy cognitive function over 60 years old as their screening test for Dementia and to select those who are recommended the clinical treatment. Methods: The tests were conducted in four areas: suburbs of large cities, urban areas of medium-sized cities, small cities, and rural / fishing village areas. The test paper, test environment such as lighting and room temperature, level of testers, ratio of test supervisors, test execution tools, etc. were standardized. The diagnosis was made based on whether the test results corresponded to Exclusion conditions and whether INDEX1 was average-1.5SD or less. For those who corresponded to this, we gave advice to encourage the clinical treatment. Results: A total of 1325 people were tested. A total of 285 people, 199 who met the Exclusion conditions and 86 who had an INDEX 1 of average-1.5SD or less, were extracted for the clinical treatment. The average extraction ratio was 21.5%. Conclusions: The extraction ratio of people who were judged to have correct self-proclaimed health of cognitive function decreased as the elderly became older, that is, the older they became, the more likely they seemed to become overconfident.